2020
DOI: 10.3389/fvets.2020.00499
|View full text |Cite
|
Sign up to set email alerts
|

Early Stage Development of a Newcastle Disease Vaccine Candidate in Corn

Abstract: Newcastle disease (ND) is a viral disease that causes labored breathing, periorbital oedema, and ataxia in the majority of avian species. The available vaccines against Newcastle disease virus (NDV) are limited, owing to their low reactivity and multiple dosage requirements. Plant-based machinery provides an attractive and safe system for vaccine production. In the current study, we attempted to express fusion (F) and hemagglutinin-neuraminidase (HN) proteins (the protective antigens against NDV) under constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Despite early work showing the viability of displaying NDV epitopes using CMV [ 160 , 161 , 162 ], most research into plant-derived NDV vaccines has focussed on expression of HN or F subunits. Various expression hosts have been explored for NDV vaccine production including potato [ 163 ], rice [ 164 ], maize [ 165 , 166 ], rapeseed [ 167 ], N. benthamiana [ 168 ], N. tabacum [ 169 ], and tobacco cell culture [ 170 ] with varying success. Modifications to constructs, such as the use of appropriate signal peptides and inclusion of ER retention signals, can enhance NDV antigen yield [ 168 ]; however, the highest reported accumulation of NDV antigen stands at 3% of total soluble protein in maize [ 165 ], with more typical yields reported across multiple plant species ranging from 0.18–0.8% of total soluble protein [ 166 , 167 , 170 ] and some yielding below 0.07% [ 169 ].…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite early work showing the viability of displaying NDV epitopes using CMV [ 160 , 161 , 162 ], most research into plant-derived NDV vaccines has focussed on expression of HN or F subunits. Various expression hosts have been explored for NDV vaccine production including potato [ 163 ], rice [ 164 ], maize [ 165 , 166 ], rapeseed [ 167 ], N. benthamiana [ 168 ], N. tabacum [ 169 ], and tobacco cell culture [ 170 ] with varying success. Modifications to constructs, such as the use of appropriate signal peptides and inclusion of ER retention signals, can enhance NDV antigen yield [ 168 ]; however, the highest reported accumulation of NDV antigen stands at 3% of total soluble protein in maize [ 165 ], with more typical yields reported across multiple plant species ranging from 0.18–0.8% of total soluble protein [ 166 , 167 , 170 ] and some yielding below 0.07% [ 169 ].…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
“…As the main target for edible NDV vaccines are farmed poultry, seed-based antigen production has great appeal given both the ease of introduction into the diet via existing feeding methods, and the long-term stability of recombinant antigens in seeds stored under ambient conditions [ 100 ]. For NDV, chicks fed transgenic rapeseed or maize seeds produce antibodies against both HN and F proteins when these are expressed as fused ectodomains [ 167 ] or by co-expression of subunits via a single plasmid [ 166 ]. However, antibody responses tended to be significantly slower and less robust than those stimulated by existing commercial vaccines.…”
Section: Newcastle Disease Virusmentioning
confidence: 99%
“…Results showed approximately 7 and 28 folds higher expressions of F and HN genes, respectively. Their analysis showed that chicken fed with these transgenic leaves produced specific antibodies against NDV antigen proteins (Shahid et al 2020).…”
Section: Oral Edible Vaccinesmentioning
confidence: 99%
“…Till now, variety of vaccines against veterinary diseases have been expressed using plant tissues as bioreactor [5]. The proof-of-concept for such studies has already been accomplished in previous studies and plants have been found suitable host for expression of edible vaccines for Newcastle disease [6], influenza, Ebola, infectious bronchitis virus (IBV), infectious bursal disease virus (IBDV) in chickens [7]. The plant made ZMapp antibodies against Ebola and influenza were not only encouraging but also paved a way for plants to be further utilized as bioreactor to combat infectious diseases in cost effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, poultry is the largest livestock group, and according to estimates with market value of $309 billion in 2019 and expected to grow nearly 6% annually till 2023 (Poultry world, 2019). The most prevalent problem in poultry especially at large scale setup includes zoonotic diseases which not only is threat to poul-try producers but also is a great risk for poultry genetic resources [6]. Thus, suitable veterinary strategies against such diseases are in crucial need of poultry setups.…”
Section: Introductionmentioning
confidence: 99%